Peran Guru Dalam Implementasi Pembiasaan Disiplin Anak Usia Dini Di TK Tawa gere - Rerek Kesen, Maria; Kamelia Olga Litna; Ronald Dwi Ardian Fufu; Theodorina Novyani Seran (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the role of teachers in the implementation of discipline habituation among early childhood learners at TK Tawa Gere. This research employed a descriptive qualitative approach involving two teachers as research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing and verification. The findings revealed that teachers had carried out their roles in implementing discipline habituation through four main roles: role models, guides, implementers, and facilitators. As role models, teachers demonstrated disciplined behavior that could be imitated by children in their daily activities. As guides, teachers provided direction, reminders, and assistance to help children understand and follow established rules. As implementers, teachers consistently carried out various discipline habituation activities through daily school routines. As facilitators, teachers provided a well-organized, safe, and comfortable learning environment supported by learning facilities, classroom rules, and activity schedules that helped children develop disciplined behavior. Therefore, the implementation of discipline habituation for early childhood learners at TK Tawa Gere has been carried out effectively through the active involvement of teachers in both learning activities and daily routines at school.